Phylogenetic Grouping and Antibiogram of ESBL-Producing Escherichia coli Isolated from Bovine Mastitis - Tarazi, Y. H.; Gharaibeh, M. H.; Al-Hurani, H. A.; Ismail, Z. (Faculty of Animal Science, Bogor Agricultural University, 2023)
Escherichia coli (E. coli) is a major cause of mastitis in dairy cattle. Multidrug resistant E. coli poses an important public health threat due to the widespread antimicrobial resistance genes that can transmit to human pathogenic E. coli through consuming contaminated milk. This study aimed to determine the phylogenetic groups and antimicrobial resistance profile of E. coli isolates from bovine clinical mastitis cases. A total of 380 milk samples were collected from dairy farms in Jordan. E. coli was cultured using routine bacterial culture methods and identified initially based on morphological and biochemical characteristics. Suspected bacteria were then confirmed by detecting 16s rRNA gene using traditional PCR methods. The phylogenetic grouping was performed using triplex PCR. The antimicrobial resistance profile was determined using a disc diffusion test followed by the double disc diffusion test to detect ESβLs-producing strains and the syndromic multiplex PCR (mPCR) to detect ESβLs genes. A total of 74 (19.4%) of E. coli strains were isolated from the collected milk samples. The majority of the isolates (52 or 70%) belonged to phylogenetic group A, followed by 13 (17.5%), 7 (9.5%), and 2 (2.7%) isolates that belonged to phylogenetic groups D, B1, and B2, respectively. Sixty-three (85.1%) isolates showed resistance to at least 2 antimicrobial agents, with the highest resistance rates detected against amoxicillin (94.6%), tetracycline (75.7%), and streptomycin (66.2%). Sixty-three (85.1%) isolates showed resistance to at least 2 antimicrobial agents and 23 (31%) isolates showed resistance to at least 2 beta lactam antimicrobial agents. Twenty-two out of 23 (95.6%) of multi-beta lactam resistant isolates were ESβL positive, 22 isolates (100%) carried blaCTX-M gene, and 20 isolates (86.9%) carried the blaTEM gene, while none of the isolates carried the blaSHV gene. The results of this study demonstrate a high prevalence of multidrug resistant, ESβLs-producing E. coli in bovine mastitis, which may represent a serious threat to public health due to the high risk of dissemination of antimicrobial resistance genes through consumption of contaminated milk.